Women as Commodity in the Iraqi Theatre with reference to Bateekh Fee Al Mareekh [Watermelon on Mars] - Niama, Majid Hameed (مجلة دراسات في التاريخ والآثار, 2020)
Introduction :The present paper aims to examine the way women are introduced, manifested and treated as commodities in Bateekh Fee Al Mareekh, a play performed at Al Najah Theatre in the capital Baghdad in 2013. The consumer/ commodity relationships are very palpable in the performance. Thus I argue that the performance defines women as mere commodities whose roles are prescribed by the male(s) to win the audience’s attention (tickets!). The analysis of the performance is thoroughly informed by Luce Irigaray’s ‘Women on Market’, an essay in her influential book The Sex Which is Not One. Considering the Iraqi conservative culture Bateekh Fee Al Mareekh violates the social norms since the performance purely objectifies women and, thus, signifies men’s ultimate superiority and women’s deficiency. The performance exhibits sexual lust, seduction and flirtations as components which altogether lead up to gender subjugation. Accordingly, spirituality, genuine love, and intellectual banter do not exist. Finally, it is very apt to argue that the performance is mainly intended to commercialise the female body and structurally built on the disavowal of women’s identity